Obstructive Sleep Apnea Syndrome and Sleep Efficiency in Patients With Ankylosing Spondylitis - In, Erdal; Turgut, Teyfik; Gulkesen, Arif; Gundogdu, Baris (Turkish League Against Rheumatism, 2015)
Objectives: This study aims to determine the prevalence of obstructive sleep apnea syndrome (OSAS) and assess sleep efficiency in patients with ankylosing spondylitis. Patients and methods: A total of 42 patients (36 males, 6 females; mean age 39.4 +/- 9.1 years; range 23 to 63 years) with ankylosing spondylitis were included in this study. Demographic data, spinal mobility measurements, disease activity measurements, and sleep questionnaire results were recorded for each patient. All subjects underwent an overnight polysomnography test and their sleep records were evaluated. Results: Polysomnography test revealed OSAS in 13 (30.9%) patients. Patients with OSAS had a significantly greater occiput-to-wall distance and neck circumference (p=0.025 and p=0.004, respectively). In addition, there was a positive correlation between apnea hypopnea index and occiput-to-wall distance and neck circumference (r=0.355, p=0.021; r=0.413, p=0.007, respectively) whereas apnea hypopnea index and body mass index did not significantly correlate. Conclusion: Our study showed that patients with ankylosing spondylitis had higher OSAS prevalence than reported in the general population. Furthermore, OSAS prevalence accordingly increased with the severity of cervical vertebral involvement.
Keywords: Ankylosing spondylitis; obstructive sleep apnea syndrome; polysomnography; sleep efficiency